2005
DOI: 10.1080/13546780442000169
|View full text |Cite
|
Sign up to set email alerts
|

Properties, categories, and categorisation

Abstract: We re-evaluate existing data that demonstrate a large amount of variability in the content of categories considering the fact that these data have been obtained in a specific task: the production of features of single isolated categories. We present new data that reveal a large consensus when participants have to judge whether or not a given feature is characteristic of a category and we show that classification tasks produce an intermediate level of consensus. We argue that the differences observed between ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 57 publications
0
7
0
2
Order By: Relevance
“…When studying how flavours or aromas are conceptualised and categorised, an alternate method for considering the data from the usual multi-dimensional space is to consider a tree structure (Lawless, 1997, p. 161). A tree structure gives an hierarchical structure that is broad and flat like a two-dimensional map, and contains super-ordinate nodes with degrees of nesting, based on semantic networks of categories and properties (Poitrenaud, Richard, & Tijus, 2005). Urdapilleta et al (2006), in a study of odour classification using floral fragrances and treestructure methodology, demonstrated that olfactory properties were classified as an hierarchically-arranged semantic network when participants were instructed to sort olfactory terms as a function of their specificity or generality.…”
Section: Introductionmentioning
confidence: 99%
“…When studying how flavours or aromas are conceptualised and categorised, an alternate method for considering the data from the usual multi-dimensional space is to consider a tree structure (Lawless, 1997, p. 161). A tree structure gives an hierarchical structure that is broad and flat like a two-dimensional map, and contains super-ordinate nodes with degrees of nesting, based on semantic networks of categories and properties (Poitrenaud, Richard, & Tijus, 2005). Urdapilleta et al (2006), in a study of odour classification using floral fragrances and treestructure methodology, demonstrated that olfactory properties were classified as an hierarchically-arranged semantic network when participants were instructed to sort olfactory terms as a function of their specificity or generality.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth module is the cognitive and goal-oriented KnowHow module that is the built-in [mental model] of the task, made of the sub-goals structure, linking sub-goals to objects (not the reverse according to the object primacy [21]). This mental model, of a schema form, entails heuristics, inferences and planning by both top-down (the task goal) and bottom-up processes (perception of task objects) by simultaneously establishing the causal links between objects and the sub-goals structure.…”
Section: Modeling Know-how For Assessmentmentioning
confidence: 99%
“…Even a cursory review of literature in the area of categorisation theory [12,19,30,33,39,48,50] is enough to recognise that this is a difficult and complex topic. The normative nature of quantitative and qualitative research was highlighted by Creswell [10] who emphasised that the utility of 'quantitative' and 'qualitative' as descriptors of research has tended to be rejected by mixed methods researchers 'in favour of a continuum for presenting qualitative and quantitative differences' (p. 273).…”
Section: Categorisation Theorymentioning
confidence: 99%